Ethical leadership, ethical leadership climate and employee moral effectiveness : a social learning perspective - Ayodele, Freida Ozavize; Hasnah, Haron; Ishak, Ismail (KnE Social Sciences, 2019)
The study employs social learning theory (SLT) to investigate the impact of virtue and tone based ethical leadership on the subordinates moral outcome in institutions. Data were collected from a survey of 182 academic staff in a university in Africa. The partial least squares structural equation modeling (PLS-SEM) is the data analytic technique employed to test the research model. The findings suggest that virtue-based academic ethical leadership and ethical leadership climate positively influence employee moral effectiveness. Academic ethical leadership was found to have a profound indirect significant influence on employee moral effectiveness and academic ethical leadership. The research is substantial and would be of interest to educational policymakers, academic leaders and government in resolving ethical issues.